The method of temporary growth zone block in treating low extremity deformities in children (a review of literature) - Korzh, Mykola; Khmyzov, Sergey; Korolkov, Oleksandr; Yershov, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Process control of bone growth in children used to correct deformations of long bones of the lower extremities. The article provides an overview of the scientific literature method of temporarily blocking the growth zone for the treatment of lower limb deformities in children. The indications and contraindications for the use of the method described surgical technique. In analyzing the results of using the method presented in various deformities of the lower extremities, which opens perspectives chosen direction in the treatment of deformities in children.